MYeHALAL System Usage During the Covid-19 Pandemic: Proposing a Socio-Technical Model to Enhance the Certifier’s Role - Arif, Sazelin; Bakar, Nurdinah Abu; Sidek, Safiah; Al-Shami, Samer Ali Hussin (International Journal of Membrane Science and Technology, 2023)
The Coronavirus Disease 2019 (COVID-19) pandemic has disrupted Malaysian halal certification process. With lockdowns and travel restrictions in place, halal certification bodies have had to adapt to new ways of conducting inspections and audits. This has led to delays and backlogs in the certification process. The purpose of this study is to propose a socio-technical model that will enhance the role of the certifiers in the MYeHALAL system during the Covid-19 pandemic. The system aims to make halal certification more accessible in Malaysia. However, it appears that this endeavour is difficult to achieve, considering the discouraging acceptance of the users. The Covid-19 pandemic makes the halal application process even more difficult as not all halal certification application processes can be done online. Semi-structured interviews were conducted with 14 halal applicants and 3 officers from the certification bodies. To develop the model, this study used Actor-Network Theory (ANT), a theory that allows for equal consideration of human (social) and non-human (technological) elements in one analysis. The socio-technical model is derived from identified issues that led to the revelation of the three actors or elements; applicants, technology and guidelines which have a major impact on the use of the MYeHALAL system. The model will highlight the important elements that the certifiers should emphasize to improve its organizational performance and promote more sustainable use of the system particularly during the Covid-19 pandemic. This study provided new insight into enhancing the role of halal food certifiers by proposing a socio-technical model.